Ca2+ release-dependent hyperpolarizations modulate the firing pattern of juvenile GABA neurons in mouse substantia nigra pars reticulata in vitro - Yanovsky, Yevgenij; Velte, Simone; Misgeld, Ulrich (The journal of physiology, 2006)
A phasic activation of small-conductance Ca2+-dependent K+ channels (SK channels) underlies spike-afterhyperpolarizations and spike-independent, transient hyperpolarizations in juvenile substantia nigra neurons. Outward current pulses that cause the spike-independent hyperpolarizations result from ryanodine receptor-mediated Ca2+ release from intracellular stores. To study the modulation of excitability by the outward current pulses, we recorded from GABAergic pars reticulata neurons of mice at postnatal days 12-16. We induced a prolongation of SK channel open states by 1-ethyl-2-benzimidazolinone (1-EBIO). In addition to a prolongation of spike-afterhyperpolarizations, 1-EBIO (200 μm) potentiated outward current pulses by increasing their duration. Neurons were manipulated by current injection to display continuous or discontinuous discharge. Despite the prolongation of the outward current pulses by 1-EBIO, continuous action potential discharge became more regular, although its frequency declined. Durations of silent periods (periods of >2× average interspike interval) increased. Caffeine (1 mm) further increased the duration of such silent periods. Caffeine, however, had no effect at short interspike intervals (<600 ms). Cyclopiazonic acid (10 μm) silenced discharge in 1-EBIO, but discharge reappeared with the depletion of Ca2+ stores. We conclude that the modulation of excitability by an activation of SK channels through ryanodine receptor-mediated release of Ca2+ critically depends on the frequency of discharge. Outward current pulses occur only if interspike intervals exceed the duration of spike-afterhyperpolarizations. In this instance, the phasic, spike-independent activation of SK channels supports pauses to interrupt autonomous discharge in juvenile GABAergic pars reticulata neurons.